Analog-Digital Converters for Industrial Applications Including an Introduction to Digital-Analog Converters - Ohnhäuser, Frank (Springer, 2015)
This book offers students and those new to the topic of analog-to-digital converters (ADCs) a broad introduction, before going into details of the state-of-the-art design techniques for SAR and DS converters, including the latest research topics, which are valuable for IC design engineers as well as users of ADCs in applications. The book then addresses important topics, such as correct connectivity of ADCs in an application, the verification, characterization and testing of ADCs that ensure high-quality end products.